γδ T cell mediated immune responses in Disease and Therapy - T, Sree Latha; Reddy, Madhava C.; Durbaka, Prasad V.; Rachamallu, Aparna; Reddanna, Pallu; Lomada, Dakshayani (Frontiers in Immunology, 2014)
The role of γδ T cells in immunotherapy has gained specific importance in the recent years because of their prominent function involving directly or indirectly in the rehabilitation of the diseases. γδ T cells represent a minor population of T cells that express a distinct T cell receptor(TCR) composed of γδ chains instead of αβ chains. Unlike αβ T cells, γδ T cells display a restricted TCR repertoire and recognize mostly unknown non-peptide antigens. γδ T cells act as a link between innate and adaptive immunity, because they lack precise MHC restriction and seize the ability to recognize ligands that are generated during affliction. Skin epidermal γδ T cells recognize antigen expressed by damaged or stressed keratinocytes and play an indispensable role in tissue homeostasis and repair through secretion of distinct growth factors. γδ T cell based immunotherapy strategies possess great prominence in the treatment because of the property of their MHC-independent cytotoxicity, copious amount of cytokine release, and a immediate response in infections. Understanding the role of γδ T cells in pathogenic infections, wound healing, autoimmune diseases and cancer might provide knowledge for the successful treatment of these diseases using γδ T cell based immunotherapy. Enhancing the γδ T cell functions by administration of aminobisphosphonates like zoledronate, pamidronate and bromohydrin pyrophosphate along with cytokines and monoclonal antibodies shows a hopeful approach for treatment of tumors and infections. The current review summarizes the role of γδ T cells in various human diseases and immunotherapeutic approaches using γδ T cells.